Repeated Long-Term DT Application in the DEREG Mouse Induces a Neutralizing Anti-DT Antibody Response - Junhua Wang; Myriam Siffert; Markus Spiliotis; Bruno Gottstein (Journal of Immunology Research)
Regulatory T (Tregs) cells play an important role in mediating tolerance to self-antigens but can also mediate detrimental tolerance to tumours and pathogens in a Foxp3-dependent manner. Genetic tools exploiting the foxp3 locus including bacterial artificial chromosome- (BAC-) transgenic DEpletion of REGulatory T cells (DEREG) mice have provided essential information on Treg biology and the potential therapeutic modulation of tolerance. In DEREG mice, Foxp3+ Tregs selectively express enhanced green fluorescent protein (eGFP) and diphtheria toxin (DT) receptor, allowing for the specific depletion of Tregs through DT administration. We here provide a detailed overview about an important consideration that long-term administration of DT induces a humoral immune response with an appropriate production of anti-DT antibodies that can inactivate DT and thus abrogate its effect in the DEREG mouse. Additionally, we showed that anti-DT mouse serum partially neutralized DT-induced Foxp3 inhibition.